Optimization of Mathematical Literacy through the Development of Information Literacy-Based Inquiry Learning in Secondary Education - Susanti, Vera Dewi; Sukestiyarno, YL; Kharisudin, Iqbal; Agoestanto, Arief (LP. Ma'arif Janggan Magetan, 2024)
The low level of students’ mathematical literacy in Indonesia, as indicated by the results of the Minimum Competency Assessment and various previous studies, highlights the need to improve the instructional models used in schools. This study examines the validity, practicality, and effectiveness of developing Information Literacy-Based Inquiry Learning. The development model used in this study is adapted from Plomp which consists of five phases: (1) the preliminary investigation phase, (2) the design phase, (3) the realization/construction phase, (4) the testing, evaluation, and revision phase, and (5) the implementation phase. The subjects in this study were 63 grade X high school students in Madiun district. Data collection techniques used in this study were validation sheets, response questionnaires, and students' mathematical literacy tests. The average score from the teaching module validation was 3.86, categorized as good, and all validators confirmed that the developed mathematical literacy test instrument was valid. In the trial, the average score from the student response questionnaire was 4.02, which was also in the good category. The average student's mathematical literacy score in this trial was 79.5. Therefore, it can be concluded that the development of the model is valid, practical, and effective.